Effectiveness Between Virtual Reality Based Exercises Versus Conventional Exercises In Patients With Vertigo - Kshirsagar, Varun; Yadav, Trupti (Journal of Neonatal Surgery, 2025)
BACKGROUND: Benign Paroxysmal Positional Vertigo (BPPV) is a condition characterised by brief episodes of nystagmus and dizziness. There are several studies which involve simulated environment such as crossing a road, walking down the aisle or manoeuvring in a supermarket as treatment protocol in the virtual reality group which can be complex for our subset of population. So, our study involves customised videos based on principles of conventional exercises such as gaze stability and habituation exercises involving biofeedback which provide simplified commands to the rural population affected by this condition. Therefore, our study will compare the effectiveness between conventional and virtual reality-based exercises in patients with vertigo. MATERIALS AND METHODS: The population (n=34) was divided into conventional group (17) and virtual reality-based group (17). Participants with dizziness caused by central vestibular disorders (e.g., stroke, multiple sclerosis), Meniere’s disease, migraine, or severe cervical spondylosis were excluded from the study. Two validated questionnaires such as the Dizziness Handicap Inventory scale (DHI-S) and Motion sensitivity quotient (MSQ) index were used as outcome measures. RESULTS: Both groups showed improvement in both outcome measures. The mean DHI score for the conventional group pre intervention was 42 ± 2.7 and for the Virtual reality-based group was 40 ± 2.4. For MSQ, the mean score for conventional group was 25 ± 2.5 and for the Virtual reality-based group was 23 ± 2.2. But post-intervention, the mean DHI score for conventional group decreased to 38 ± 2.5 and for VRB group the score was 37 ± 2.4. Similarly, for MSQ, the mean score for conventional group was 22 ± 2.1 and for the VRB group was 20 ± 1.9. CONCLUSION: This study demonstrates that both conventional vestibular rehabilitation exercises and those enhanced by virtual reality (VR) technology resulted in improved patient reported symptoms for DHI and MSQ. While conventional methods have proven to be effective, the integration of VR offers an engaging, adaptive, and potentially more effective means of rehabilitation.